PENGEMBANGAN E-MODUL BERBASIS PROBLEM BASED LEARNING PADA MATA KULIAH KAJIAN MASYARAKAT INDONESIA - Helmi, Dewilna (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2024)
The emergence of new challenges in education presents opportunities for students to explore learning outside their field of study. Lecturers need to prepare learning materials, such as electronic modules, to help students develop critical thinking skills. The aim of this research is to develop an electronic module based on problem based learning for the Indonesian Community Studies course. The development approach used uses the R&D model. Validation results show that this electronic module received a positive assessment from content/material experts (83.57%), learning design experts (84.71%), and media experts (84%). Trials with lecturers and students also showed good quality. Thus, the results of this research confirm that the Problem Based Learning-based electronic module developed is suitable for use in the Geography Education Study Program at Pattimura University